Longitudinal changes in thyroid function in the oldest old and survival: the cardiovascular health study all-stars study - Waring, Avantika C; Arnold, Alice M; Newman, Anne B; Bùzková, Petra; Hirsch, Calvin; Cappola, Anne R (The journal of clinical endocrinology and metabolism, 2012)
Data on thyroid function in the oldest old are sparse, and existing studies show conflicting evidence on the relationship between thyroid function and mortality in this age group. We describe longitudinal changes in thyroid function in a cohort of elderly individuals and determine the relationship between thyroid function and mortality. Eight hundred forty-three participants in the Cardiovascular Health Study All Stars Study who were not taking thyroid medications and had thyroid function testing in 2005-2006 (mean age 85 yr). Thyroid-stimulating hormone (TSH), free T(4) (FT4), total T(3), and thyroid peroxidase antibody status were measured in 1992-1993 and 2005-2006. Deaths were ascertained through February 2011. There was a statistically significant 13% increase in TSH, 1.7% increase in FT4, and 13% decrease in total T(3) over the 13-yr period. Two hundred eighty-seven deaths occurred over a median follow-up of 5.1 yr. There was no association between subclinical hypothyroidism[hazard ratio (HR) 0.97, 95% confidence interval (CI) 0.66-1.43], TSH level (HR per milliunits per liter 0.94, 95% CI 0.88-1.01), or persistent thyroid peroxidase antibody positivity (HR 1.09, 95% CI 0.62-1.92), and death. However, FT4 was positively associated with death (HR per nanograms per deciliter 2.57, 95% CI 1.32-5.02). TSH increased over time in these older individuals. This elevation was not associated with increased or decreased mortality, although higher FT4 levels were associated with death. These findings raise concern for treatment of mild elevations of TSH in advanced age. Further studies are needed to determine the potential benefit of treating age-related changes in thyroid function.